Oral microbial dysbiosis linked to worsened periodontal condition in rheumatoid arthritis patients - Corrêa, Jôice Dias; Fernandes, Gabriel R.; Calderaro, Débora Cerqueira; Mendonça, Santuza Maria Souza; Silva, Janine Mayra; Albiero, Mayra Laino; Cunha, Fernando Q.; Xiao, E.; Ferreira, Gilda Aparecida; Teixeira, Antônio Lúcio; Mukherjee, Chiranjit; Leys, Eugene J.; et al. (Scientific reports, 2019)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by joint inflammation. Individuals with RA have a higher risk of periodontitis and periodontitis has been linked to RA through the production of enzymes by periodontal pathogens that citrullinate proteins. This linkage is supported by findings that periodontitis is associated with increased RA severity and treatment of periodontitis can improve the symptoms of RA. The possible mechanism for this association is through dysbiosis of the oral microbiota triggered by RA-induced systemic inflammation. We examined the RA status of subjects by measuring the number of tender and swollen joints, anti-citrullinated protein antibody and rheumatoid factor. Periodontal disease status and salivary cytokine levels were measured, and dental plaque analyzed by 16S rRNA high throughput sequencing. RA patients had a higher bacterial load, a more diverse microbiota, an increase in bacterial species associated with periodontal disease, more clinical attachment loss, and increased production of inflammatory mediators including IL-17, IL-2, TNF, and IFN-γ. Furthermore, changes in the oral microbiota were linked to worse RA conditions. Our study provides new insights into the bi-directional relationship between periodontitis and RA and suggest that monitoring the periodontal health of RA patients is particularly important.